Effective Methods for Software and Systems Integration - Summers, Boyd (Auerbach Publications, 2016)
Before software engineering builds and installations can be implemented into software and/or systems integrations in military and aerospace programs, a comprehensive understanding of the software development life cycle is required. Covering all the development life cycle disciplines, Effective Methods for Software and Systems Integration explains h.